Rychlost učení vícevrstvé sítě - Maceček, Aleš (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2011)
Teoretický rozbor umělých neuronových sítí, zvláště jejich typů topologií a učení sítí. Zvláštní zaměření je na vícevrstvou neuronovou síť s učením backpropagation. Uvedený algoritmus učení backpropagation jednoduché sítě společně s popisem parametrů ovlivňujících učení sítě a také metody zhodnocení kvality naučení sítě. Definice momentů invariantních na otočení, posun a změnu měřítka. Optimalizace parametrů neuronové sítě k nalezení nejrychleji učící se neuronové sítě, a také sítě s nejlepší hodnotou rozpoznání vzorů písmen z testovací množiny.

Theoretical study about neural networks, especially their types of topologies and networks learning. Special attention is attended to multilayer neural network with learning backpropagation. Introduced learning algorithm backpropagation of simple networks in conjunction with descriptions of parameters affecting network learning also methods to exaluation quality of network learning. Definition moment invariants to rotation, translation and scaling. Optimalization parameters of neural networks to find the network which has the fastest learning and also the networks with the best value of recognition patterns of letters from testing set.
Speed of learning multilayer network
Keywords: Neuron; neuronová síť; backpropagation; momentové invarianty; rozpoznávání; klasifikace vzorů; Neuron; neural network; backpropagation; moment invariants; recognition; pattern classifications